2020
DOI: 10.1097/cce.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Tracheostomy for Prolonged Respiratory Wean in Critically Ill Coronavirus Disease 2019 Patients: A Machine Learning Approach

Abstract: Objectives: To propose the optimal timing to consider tracheostomy insertion for weaning of mechanically ventilated patients recovering from coronavirus disease 2019 pneumonia. We investigated the relationship between duration of mechanical ventilation prior to tracheostomy insertion and in-hospital mortality. In addition, we present a machine learning approach to facilitate decision-making. Design: Prospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
16
1
1
Order By: Relevance
“…Of these, 46 studies met inclusion criteria. 7 further studies were removed with shared data, leaving 39 studies for meta-analysis 16 , 17 , 18 , 19 , 20 , 21 , 22 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 46 studies met inclusion criteria. 7 further studies were removed with shared data, leaving 39 studies for meta-analysis 16 , 17 , 18 , 19 , 20 , 21 , 22 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…8 A study of 87 tracheostomized patients did find that only 7 died after receiving a tracheostomy. 11 However, the present study had a higher rate of mortality as 25 patients died after receiving a tracheostomy; COVID-19 related issues caused the majority of the cases. Moreover, the present study showed that an uptrending CRP level was the only factor significantly associated with mortality.…”
Section: Resultsmentioning
confidence: 53%
“…This finding was in agreement with another study that concluded that both CRP and PEEP levels were independently associated with mortality in tracheostomized patients. 11 Study limitations. The study population comprised patients from a single hospital in Riyadh, Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of 61 peer-reviewed studies were included in the final analysis (Fig. 1A) 10,12,13,21–78 . Of these final 61 studies, 11 studies were conducted in China, 3 were conducted in America (2 studies from South America and 1 study from Central America), 17 involved centers in the United States, 16 involved centers in Europe, 3 involved centers in Canada, 9 involved centers in Asia, and 2 were based on multinational collaborations (one was between the United Kingdom and Ireland, and the second was between the United States, Europe, Canada, and Japan).…”
Section: Resultsmentioning
confidence: 99%